Organisational learning and food safety crises : a critical case study of the Sanlu and Fonterra crises : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, New Zealand - Ding, Guoyu (Massey University, 2022)
This study explores crisis-induced organisational learning in the Chinese and the New Zealand food safety authorities, or CFSA and NZFSA. While many crisis management scholars have sought to examine food safety crises, including the 2008 Sanlu melamine infant formula scandal and the 2013 Fonterra botulism scare, from the perspective of business organisations, food safety government agencies’ role in handling such crises, especially crisis-induced learning in the food safety authorities to prevent or better prepare for future crises, has been neglected. This thesis seeks to address this research gap by examining the two food safety crises under the lens of crisis-induced organisational learning to investigate changes in CFSA and NZFSA triggered by the biggest-ever food safety crises happened in China and New Zealand. Qualitative content analysis approach is employed to analyse the data corpus consisting of news articles and government documents recording the dairy food safety incidents and their socio-economic and political contexts and ensuing policy changes. A comparison between the two cases offers a deep understanding of the dairy food safety landscapes in the two countries and approaches employed by the government agencies in handling the dairy food safety crises. It also provides insights into dynamics of internal and external factors facilitating or inhibiting crisis-induced organisational learning in the two dairy food safety authorities. Though the two crises in this research have different socio-economic and political roots, they both caused unprecedented reputational damage not only to the dairy industries but to the whole food sectors in China and New Zealand. This research identifies multiple loopholes and underlying problems in the two dairy food safety regulatory systems leading to the incidents in question. It also finds systemic changes in the food safety authorities and the dairy food safety regulatory systems to address the loopholes. Political pressure and social emotion provoked by the dairy product crises are found to be the main factors facilitating learning in the public organisations. Conflict of interest incorporated into the dairy food safety system is seen as a key factor inhibiting deep learning in the two food safety authorities. This study therefore argues double-loop learning needs to happen in CFSA and NZFSA to uproot the underlying problem that led to lax regulation and other dairy food safety regulatory problems.
Keywords: Food adulteration and inspection; Dairy products; Contamination; Administrative agencies; Management; New Zealand Food Safety Authority; Organizational learning; China; New Zealand; dairy food safety crisis; food safety authority; food safety crisis management; crisis-induced organisational learning; single/double-loop learning; 470108 Organisational, interpersonal and intercultural communication